Batwing Technique in Large Volume Excision of Breast Lesions: Case Report - Khanal, Suman; Singh, Yogendra P; Sharma, Rashmi (Journal of Institute of Medicine Nepal, 2019)
Oncoplastic surgical techniques are seeing widespread use for excision of large volume breast lesions. Batwing technique is one of the volume displacement techniques that can be used to manage lesions in central quadrant of the breast. Such techniques are still underused in Nepal. Here we present three cases with large volume benign breast lesions managed with simple, easy-to-learn technique of Batwing oncoplasty.